2007
DOI: 10.1002/bip.20815
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic and molecular modeling studies of the interaction between cytidine and human serum albumin and its analytical application

Abstract: In this study, the interaction between cytidine and human serum albumin (HSA) was investigated for the first time by fluorescence spectroscopy in combination with UV absorption spectrum and molecular modeling under simulative physiological conditions. Experimental results indicated that cytidine had a strong ability to quench the intrinsic fluorescence of human serum albumin. The binding constants (K) at different temperatures, thermodynamic parameter enthalpy changes (DeltaH) and entropy changes (DeltaS) of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In this context, one should consider the possibility of binding of citicoline to plasma proteins such as albumin. Albumin binding has been reported for cytidine [74] and also for sphingosylphosphorylcholine [75], a compound remotely similar to citicoline. If intact citicoline binds to albumin, its hydrolysis could be retarded and its action as a signalling molecule could be prolonged.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…In this context, one should consider the possibility of binding of citicoline to plasma proteins such as albumin. Albumin binding has been reported for cytidine [74] and also for sphingosylphosphorylcholine [75], a compound remotely similar to citicoline. If intact citicoline binds to albumin, its hydrolysis could be retarded and its action as a signalling molecule could be prolonged.…”
Section: Unresolved Issuesmentioning
confidence: 99%
“…Indeed, experiment has shown that at least with certain highly anisotropic materials, such as LiFePO4, the shrinking core model is not valid. [4][5][6] On the other hand, the model is widely assumed to be correct for larger spherically-shaped agglomerated secondary particles, 5 that is, agglomerated particles can be assumed to be approximately isotropic and homogeneous on the size scale of the particle. Recently, however, some data have been presented that contradicts this approximation.…”
mentioning
confidence: 99%